Ginseng Omics for Ginsenoside Biosynthesis - Yin, Xianmei; Hu, Haoyu; Shen, Xiaofeng; Li, Xiangyan; Pei, Jin; Xu, Jiang (Current Pharmaceutical Biotechnology, 2021)
Ginseng, also known as the king of herbs, has been regarded as an important traditional medicine for several millennia. Ginsenosides, a group of triterpenoid saponins, have been characterized as bioactive compounds of ginseng. The complexity of ginsenosides hindered ginseng research and development both in cultivation and clinical research. Therefore, deciphering the ginsenoside biosynthesis pathway has been a focus of interest for researchers worldwide. The new emergence of biological research tools consisting of omics and bioinformatic tools or computational biology tools are the research trend in the new century. Ginseng is one of the main subjects analyzed using these new quantification tools, including tools of genomics, transcriptomics, and proteomics. Here, we review the current progress of ginseng omics research and provide results for the ginsenoside biosynthesis pathway. Organization and expression of the entire pathway, including the upstream MVA pathway, the cyclization of ginsenoside precursors, and the glycosylation process, are illustrated. Regulatory gene families such as transcriptional factors and transporters are also discussed in this review.
Keywords: Panax ginseng